Aspectos reprodutivos de harttia carvalhoi miranda ribeiro, 1939, um pequeno loricariídeo de riachos do leste da serra da mantiqueira, SP, Brasil - Biagiotto, Renan Hohendorff [UNESP]; Rondineli, Giulianna; Carmassi, Alberto Luciano [UNESP]; Braga, Francisco Manoel de Souza [UNESP] (FapUNIFESP (SciELO), 2012)
The aim of this work was to present the reproductive aspects of Harttia carvalhoi Miranda Ribeiro, 1939, a small loricariid whose distribution is restricted to the area of drainage basin of the Paraíba do Sul river. A total of 110 specimens of H. carvalhoi were captured. The reproductive period happens from September to February. A total spawning type was identified and fecundity rate ranged from 16 to 106 oocytes. This type of study is important, since fecundity is a specific feature and is adapted to the conditions of the life cycle, varying with growth, population density, food availability and mortality rate. We also emphasize the importance of this study, since there are no previous studies about the reproduction of this species.
Reproductive aspects of harttia carvalhoi miranda ribeiro, 1939, a small loricariid from streams of serra da mantiqueira eastern, SP, Brazil
Keywords: Brazil; Fecundity; Loricariinae; Reproductive period; Sex ratio